Achieving ambidexterity in internationalization: analysis of how SMEs cope with tensions between organizational agility–efficiency - Priyono, Anjar; Idris, Fazli; Abdul Halim Lim, Sarina (Multidisciplinary Digital Publishing Institute, 2020)
This study aims to examine how small and medium enterprises manage the tensions between organizational agility and efficiency. Organizational agility is a multidimensional concept where each of its components can interact differently with efficiency. The tensions between other capabilities have been explored in many previous studies, yet there is a lack of research exploring the roots of the tensions between organizational agility and efficiency, how the actors interpret these tensions and what dimensions of organizational agility are causing the tensions. A multiple case study research design with an inductive approach was used to explore how two SMEs manage the tensions between organizational agility and efficiency to serve customers from abroad. Despite the relationship between the agility and efficiency seeming contradictory, our analysis demonstrated that the interaction between the two concepts is complex, depending on the object of the tensions, the actors involved and the context. In fact, two actors at the same level of the organizational hierarchy can have identical perceptions about a tension, but they can arise from different logical reasoning. Moreover, due to the multidimensionality of organizational agility, a meta-capability of organizational agility is more likely to dominate the interaction with efficiency. This study contributes to the limited empirical evidence on how actors in SMEs perceive and manage the various tensions emerging from organizational agility and efficiency.